GAGURITAN RUSAK BULELENG SEBUAH KAJIAN NILAI-NILAI - Kertiasih Ni Nyoman (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2020)
Gaguritan Rusak Buleleng, Gedong Kirtya collection can provide an overview of heroic historical events in North Bali. The incident occurred in 1846, causing the kingdom of Buleleng fell into the hands of the Dutch invaders. At that time the situation showed that Dutch political power was expanding its influence in the Indonesian Archipelago. Bali began to be targeted by the colonial government in the mid-19th century. The values that can be extracted from the GRB story can be mentioned: the value of unity, togetherness, leadership, educational values, religious values, political / diplomacy values, and the value of the competition for political power between political forces. As part of the content analysis approach model, it can be mentioned, various contexts of the situation, cultural value systems influence in it. In that connection, it seems to influence the system of values of harmony, unity of the Balinese, the value of the political competition of the kings of Bali, the value of traditional Balinese traditions, and the colonial political system that is developing.